PENGARUH KESELAMATAN DAN KESEHATAN KERJA TERHADAP KOMITMEN ORGANISASIONAL KARYAWAN MELALUI KEPUASAN KERJA (Studi Pada Karyawan PT Semen Indonesia (Persero) Tbk) - YUSTINA ; Prof. Noermijati, SE., MTM
This research aims to (1) determine whether occupational safety and health affects _x000D_ organzational commitment directly, (2) determine whether occupational safety and_x000D_ health affects job satisfaction directly, (3) reveal whether job satisfaction affects_x000D_ organizational commitment diretly, (4) reveal whether occupational safety and_x000D_ health affects organizational commitment indirectly through job satisfaction. The_x000D_ research is explanatory in nature and intended to explain the relation between_x000D_ variabels. The Population of this research involves regular employees of PT Semen_x000D_ Indonesia (Persero) Tbk. The sample consists of 152 employees taken by using_x000D_ proportional random sampling. Further, the data were analysed with descriptive_x000D_ measure and path analysis using SPSS 23. It is found that (1) occupational safety_x000D_ and health directly influenced organizational commitment, (2) occupational safety_x000D_ and health directly influenced job satisfaction, (3) job satisfaction directly_x000D_ influenced organizational commitment, and (4) occupational safety and health_x000D_ indirectly influenced organizational commitment through job satisfaction _x000D_ _x000D_ Keywords: Occupational Safety and Health, Organizational Commitment, Job _x000D_ Satisfaction